Prospective Study of Alcohol Use and Hearing Loss in Men - Curhan, Sharon G. (2011)
OBJECTIVE: Hearing loss is a common and disabling sensory disorder, yet prospective data on potentially modifiable risk factors are limited. Previous studies suggest that alcohol consumption may influence the development of hearing loss, yet results have been inconsistent. The purpose of this study was to prospectively examine the relation between alcohol use and hearing loss in men. DESIGN: We examined prospectively the independent association between alcohol intake and self-reported professionally diagnosed hearing loss in 26,809 men aged 40–74 years at baseline in 1986. Study participants completed detailed questionnaires at baseline and every two years thereafter. Incident cases of hearing loss were defined as those professionally diagnosed after 1986. Cox proportional hazards multivariate regression was used to adjust for potential confounding factors. RESULTS: During 386,081 person-years of follow-up, 3447 incident cases of hearing loss were reported. Overall, there was no association between level of alcohol intake and risk of hearing loss. Compared to those who did not consume alcohol, the multivariate-adjusted hazard ratios (95% CI) were 1.00 (0.89–1.12) for those who consumed 5.0–9.9 grams/day, 1.08 (0.96–1.21) for 10.0–14.9 grams/day, and 0.98 (0.85–1.13) for 30.0–49.9 grams/day. The results did not differ by age group or folate intake. Among those with lower intake of vitamin B12, however, higher consumption of alcohol, specifically liquor, was associated with an increased risk of hearing loss. CONCLUSIONS: Our data suggest that low or moderate alcohol consumption does not influence the risk of hearing loss in older men. A possible relation between vitamin B12 intake, alcohol consumption and hearing loss merits further investigation.